Gradable Possibility and Epistemic Comparison. (15th November 2018) - Herburger, Elena; Rubinstein, Aynat
Abstract: While some modals readily appear in comparative constructions and are clearly gradable (e.g., likely as in p is more likely than q ), the gradablity of possibility modals (e.g., possible ) is controversial. We argue that one of the major reasons to think that possibility modals can be graded, namely the appearance of German possibility modals like möglich 'possible' and kann 'can' in a special comparative construction involving eher, does not withstand closer scrutiny. We argue that eher is not a simple comparative marker and propose an analysis of eher möglich in which degrees of epistemic commitment are compared, not degrees of possibility. Our analysis explains similarities between eher and epistemic modals in terms of individual orientation, inference, and interaction with attitude predicates. Certain striking similarities between eher and metalinguistic comparatives are discussed, with notable differences in modality type and distribution arguing against the conflation of these two constructions and contributing to a deeper understanding of special comparative constructions across languages.